Digital Zakat Payment: User Experience of Islamic Bank in Indonesia - Dwi Santosa Pambudi; Rofiul Wahyudi (At-Taqaddum, 2022)
Zakat plays an important role in Islamic social financial institutions. So far, the receipt and payment of zakat has been carried out in many areas, starting from places of worship, social organizations, zakat institutions, to business institutions. In the modern era, the number of media and digital zakat payment centers has mushroomed, so that people have several alternatives. Therefore, this study aims to explore the experience of users of digital zakat services, especially Islamic banks in Indonesia. To achieve research objectives, the authors use descriptive analysis. The research was conducted by distributing online questionnaires using the Google form. The questionnaire survey was conducted for five weeks, from July to August 2022. The sample for this study was 100 digital payment users at Islamic banks. Users are divided into three sections; they are users of m-banking, ATM, and both. Limitations/implications of this study using a relatively small sample size compared to the size of the Indonesian population. Thus, the results must be interpreted with the observed sample. Practical Implications Islamic banks should ensure that their system is easy for people to make zakat payments online. Originality/value This study offers new insights related to quantitative studies on digital zakat and the behavior of zakat payers, especially in Indonesia.